ON THE DIVISION OF THINGS INTO IMMOVABLE AND MOVABLE - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Legal theory has long been dominated by the opinion that immovable things are those that cannot be moved from one place to another without damaging their essence. Scientific achievements and technical progress have made that traditional notions anachronistic. There are devices, equipment and processes that make it possible to transmit what once could not be transmitted without breaking it down into components (elements).Of essential importance is not the possibility of physical transfer of thing, but the determination of its place, i.e., locating (locus). According to the laws of classical physics, no body can be in two different places at the same time. A thing will be considered immovable if it is permanently positioned in a certain space and time (situs), i.e. if it is stationary (statio, stationarius). Some things have this characteristic due to their physical nature (res naturaliter immobiles) e.g. land, and some by the will of the owner (res civiliter immobiles) e.g. a prefabricated house or by rules determined by state authorities, e.g. a sculpture of a historical person in a public square.It is obvious that a thing should be considered immovable and relevant from the point of view of property law, if two requirements are cumulatively fulfilled. One of them is physical (stationarity) and the other is legal (considered immovable by law).  In the modern world, special methods have been developed for the precise positioning of immovable things (real estates) and the appropriate infrastructure at the global and national (state) level, which enables this. On the Planet, the position of any stationary object can be precisely determined using the Global Positioning System - GPS. Based on them, users can precisely determine the geographic longitude, latitude and altitude of the place where the thing is located. The territory of the Republic of Serbia is covered by a network of permanent stations of the global positioning system - Agros. That network represents the basic geodetic infrastructure for carrying out geodetic work, as well as for supporting users in the field of agriculture, construction etc. The set of all geospatial and other data on immovable things, property rights and certain obligation rights on them, as well as on the holders of those rights registered in the public register, constitutes the real estate cadastre database. To the current level of social development and legal science, corresponds the opinion that immovable things in the sense of property law are those that are more permanently located on a precisely determined part of the surface of the planet Earth and which are considered immovable by law. Opposite to that, movable things are non-stationary, those whose position does not have to be exactly, or even determined at all, in order to be the subject of ownership, legal transactions, etc. In this paper, special attention is given to deviations from the physical requirement that must be met for the thing to be immovable, such as land with variable position (landslides and free-floating islands).  New technologies provide new opportunities and change the logic of thinking. In this context, it should be noted that apart from the GPS, there are also precise digital programs and models that enable predictive land mapping (digital land surface models for predictive mapping). By using them, it is possible to determine in advance the future positions of land and buildings on landslides, as well as the spatial coordinates of (variable) plots of land.